Teacher Creativity and Learning Technology Integration in Islamic Religious Education at Tinokkah Public Elementary School Number 104332 - Saragih, Siti Jayanti; Daulai, Afrahul Fadhila (Edumaspul: Jurnal Pendidikan, 2026)
This study aims to determine teacher creativity and the effectiveness of technology utilization in Islamic Religious Education (PAI) learning at SDN Tinokkah No. 104332, while identifying supporting and inhibiting factors in its implementation. This study uses a descriptive method with a qualitative approach. Data collection techniques were carried out through observation, interviews, and documentation, while data analysis techniques used data reduction, data presentation, and drawing conclusions. The results show that PAI teachers have demonstrated creativity in utilizing learning technology, such as the use of PowerPoint, learning videos, and digital images to help explain abstract material so that it is easier for students to understand. The use of technology has a positive impact on the learning process, as seen from the increase in student enthusiasm, attention, and understanding of the material presented. Supporting factors include teachers' willingness to learn and innovate and school support, while inhibiting factors include limited facilities and access to technology. Thus, teacher creativity and the use of technology play an important role in improving the quality of PAI learning.